2015
DOI: 10.1038/srep08615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fe oxide on N transformations in subtropical acid soils

Abstract: Subtropical ecosystems are often characterized by high N cycling rates, but net nitrification rates are often low in subtropical acid soils. NO3−-N immobilization into organic N may be a contributing factor to understand the observed low net nitrification rates in these acid soils. The effects of Fe oxide and organic matter on soil N transformations were evaluated using a 15N tracing study. Soil net nitrification was low for highly acidic yellow soil (Ferralsols), but gross ammonia oxidation was 7 times higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Hence, physicochemical abiotic parameters might play an important role in retaining or processing NO 3 À in the upper soil layer, and the in situ 15 N tracing method is not able to differentiate between biotic or abiotic NO 3 À immobilization or processing. Therefore abiotic NO 3 À immobilization via the ferrous wheel hypothesis, Feammox or NO 3 À adsorption to variable-charge soils might also contribute to the reported NO 3 À immobilization rates (Davidson et al 2003, Lohse and Matson 2005, Jiang et al 2015.…”
Section: Comparing Lowland and Montane Mixed Forest (Lmf Vs Mmf)mentioning
confidence: 99%
“…Hence, physicochemical abiotic parameters might play an important role in retaining or processing NO 3 À in the upper soil layer, and the in situ 15 N tracing method is not able to differentiate between biotic or abiotic NO 3 À immobilization or processing. Therefore abiotic NO 3 À immobilization via the ferrous wheel hypothesis, Feammox or NO 3 À adsorption to variable-charge soils might also contribute to the reported NO 3 À immobilization rates (Davidson et al 2003, Lohse and Matson 2005, Jiang et al 2015.…”
Section: Comparing Lowland and Montane Mixed Forest (Lmf Vs Mmf)mentioning
confidence: 99%
“…Studies on Fe requirements for ammonia-oxidizing bacteria (AOB) showed that when the Fe concentration in the medium of Nitrosomonas europaea increased from 0.2 to 10 µM Fe, the activities of both ammonia monooxygenase and hydroxylamine oxidoreductase decreased (Wei et al, 2006). A recent study observed that the abundance of AOB and ammonia-oxidizing archaea (AOA) in an acidic forest soil decreased after the addition of hematite, a type of Fe oxide (Jiang et al, 2015a). Nevertheless, it is difficult to generalize the response of nitrification to Fe oxide addition under varying soil pH.…”
Section: Introductionmentioning
confidence: 99%
“…This process can also produce reactive intermediates such as nitrogen oxides (NO x ) and nitrous oxide (N 2 O) affecting air quality and global climate. The role of iron (Fe) oxides in the soil nitrification process both in anoxic (Clément et al, 2005;Yang et al, 2012;Ding et al, 2014) and oxic environments (Jiang et al, 2015a) is recognized, yet is rarely identified in biogeochemical models that predict global N cycle processes. Iron and its oxides are found in abundance in many soils, with large amounts of Fe oxides being typically found in subtropical and tropical soils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In temperate forest soils, abiotic immobilization of 15 NO3to the DO 15 N occurs within minutes (Dail et al, 2001) and is independent of soil N status, contrary to the negative correlation observed between microbial N immobilization and soil N concentration (Johnson et al, 2000). Net nitrification in subtropical acid soils was also significantly inhibited by Fe oxide addition in the form of hematite in cambisols, and AOA and AOB gene abundance decreased (Jiang et al, 2015). Total Fe concentration in the Cerrado soils studied (ranged from 46 to 375 mg dm -3 ) here were higher than the values mentioned by Jiang et al (2015) for the subtropical ferralsols with high NO3immobilization and low net nitrification, supporting the hypothesis that abiotic NO3immobilization takes place in soils from the Cerrado.…”
Section: Fementioning
confidence: 99%